A new technique of scrotoplasty following total scrotal destruction by raised rotated perineal flaps with de epithelialized borders - Ghahestani, Seyyed Mohammad; Hekmati, Pooya; Karimi, Sara (Urology Journal, 2019)
In this article we present two-year-old male patient who had history of Fournier gangrene of scrotum. Extensive perineal and scrotal debridement with suprapubic cystostomy tube insertion had been done for him in the emergency setting One year later his parents brought him back for scrotal reconstruction. A novel technique by using rotational perineal flap was used.The cosmetic result of1 months and 3 months follow up is presented in the article.